ANALISIS PEMANFAATAN INSTAGRAM DAN WHATSAPP DALAM MENINGKATKAN LOYALITAS PELANGGAN BISNIS KATERING JANLEKOH KITCHEN - Santoso , Irfan; Saptaria, Lina (Jurnal Manajemen & Bisnis Jayakarta, 2025)
Marketing communication through digital promotions using social media is very important for the success of digital marketing. The aim of this research is to analyze the use of social media Instagram and WhatsApp in digital marketing activities at Janlekoh Kitchen. This research uses a qualitative descriptive approach with a case study method. Data was obtained from informants through observation, interviews and documentation using purposive sampling and snowballing sampling techniques. The subjects of this research are business owners, managers, employees and customers of the Janlekoh Kitchen catering business. Research data analysis uses content analysis and source triangulation. Research findings show that Instagram and WhatsApp social media are effectively used to support digital promotional activities (product visualization, scheduled promotions), understand demographics and consumer behavior, get direct feedback from consumers so that it can be used to improve products and services. WhatsApp social media can support efficient communication with customers, especially in order and reservation activities, confirmation and order updates. WhatsApp groups can support effective internal coordination between team members and operational efficiency of business activities. Research findings show that social media Instagram and WhatsApp produce a significant impact on customer loyalty such as: building customer relationships, increasing customer engagement and brand loyalty, maintaining relationships with customers during and after purchase. The challenges found were data security issues, digital content management, scheduling of content presentation, customer relationship management, and developing sustainable digital communication strategies. This research is useful for practitioners and researchers on digital marketing topics in the catering industry.